Tracing heavy metals in ‘swine manure - maggot - chicken’ production chain - Wanqiang Wang (Nature Portfolio, 2017)
Abstract With the development of large-scale livestock farming, manure pollution has drawn much attention. Conversion by insects is a rapid and cost-effective new method for manure management. Swine manure conversion with maggots (Musca domestica larvae) has developed, and the harvested maggots are often used as animal feed. However, the flow of heavy metals from manure to downstream processes cannot be ignored, and therefore, heavy metal content was measured in untreated raw manure, maggot-treated manure, harvested maggots and maggot-eating chickens (chest muscle and liver) to evaluate potential heavy metal risks. The levels of zinc, copper, chromium, selenium, cadmium and lead had significant differences between untreated raw manure and maggot-treated manure. The concentrations of all detected heavy metals, except for cadmium and selenium, in maggots met the limits established by the feed or feed additive standards of many countries. The bioaccumulation factor (BAF) of heavy metals decreased with the increase of the maggot instar, indicating that heavy metals were discharged from the bodies of maggots with the growth of maggots. Also, the contents of overall heavy metals in chickens fed harvested maggots met the standards for food. In conclusion, regarding heavy metals, it is eco-safe to use maggots in manure management.